Laparoscopic Cholecystectomy Performed by Residents: A Retrospective Study on 569 Patients - Pariani, Dario (Hindawi Publishing Corporation, 2014)
Introduction. Aim of this study was to evaluate the safety of laparoscopic cholecystectomy performed by residents. Materials and Methods. We retrospectively reviewed 569 elective laparoscopic cholecystectomies. Results. Duration of surgery was 84 ± 39 min for residents versus  66 ± 47 min for staff surgeons, P < 0.001. Rate of conversion was 3.2% for residents versus 2.7% for staff surgeons, P = 0.7. There was no difference in the rates of intraoperative and postoperative complications for residents (1.2% and 3.2%) versus staff surgeons (1.5% and 3.1%), P = 0.7 and P = 0.9. Postoperative hospital stay was 3.3 ± 1.8 days for residents versus  3.4 ± 3.2 days for staff surgeons, P = 0.6. One death in patients operated by residents (1/246) and one in patients operated by staff surgeons (1/323) were found, P = 0.8. No difference in the time to return to normal daily activities between residents (11.3 ± 4.2 days) and staff surgeons (10.8 ± 5.6 days) was found, P = 0.2. Shorter duration of surgery when operating the senior residents (75 ± 31 minutes) than the junior residents (87 ± 27 minutes), P = 0.003. Conclusion. Laparoscopic cholecystectomy performed by residents is a safe procedure with results comparable to those of staff surgeons.